2009
DOI: 10.1063/1.3073715
|View full text |Cite
|
Sign up to set email alerts
|

Role of carrier reservoirs on the slow phase recovery of quantum dot semiconductor optical amplifiers

Abstract: The gain and phase recovery dynamics of quantum-dot ͑QD͒ semiconductor optical amplifiers are calculated, including all the optical transitions involved in successive carrier recovery processes. The carrier recovery dynamics of inhomogeneously broadened QDs is simulated by solving 1088 coupled rate equations. The respective contributions of QD states and quantum-well carrier reservoirs to the gain and phase changes are identified both temporally and spectrally. We show that the slow phase recovery component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…1(b 48,49 It has been reported that the electron injection rate from the singlet excited state of N719 to metal oxide electrodes is one order of magnitude faster than that from the triplet state. 38,46 Another explanation could be that both the two injection processes mostly correspond to electron injection processes from the triplet excited state due to some inhomogeneities in the TiO 2 nanoparticle surfaces, resulting in different electronic couplings between N719 and the TiO 2 . Considering the ultrafast intersystem crossing time of 100 fs from the singlet excited state to the triplet excited state in N719, the electron injection from the singlet excited state would be unfavorable if the injection time was longer than 100 fs and its component would be small.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1(b 48,49 It has been reported that the electron injection rate from the singlet excited state of N719 to metal oxide electrodes is one order of magnitude faster than that from the triplet state. 38,46 Another explanation could be that both the two injection processes mostly correspond to electron injection processes from the triplet excited state due to some inhomogeneities in the TiO 2 nanoparticle surfaces, resulting in different electronic couplings between N719 and the TiO 2 . Considering the ultrafast intersystem crossing time of 100 fs from the singlet excited state to the triplet excited state in N719, the electron injection from the singlet excited state would be unfavorable if the injection time was longer than 100 fs and its component would be small.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Drude theory, 38,41 we can consider that only free photoexcited electrons and holes are responsible for the population grating signals. 35,39,40 For bulk CdSe, the effective masses of electrons and holes are 0.13m 0 and 0.44m 0 (m 0 is the electron rest mass), respectively, 42 so both the photoexcited electron and hole carrier densities in the CdSe QDs contribute to the signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the phase response of the QD-SOA under the OP and EOP schemes is much better than that under the EP scheme. The slow phase recovery in an electrically pumped QD-SOA is attributed to a signicant contribution of the carrier reservoir in the index changes [14]. Since under the OP and EOP schemes the US and the QW state have a negligible eect on the index changes, a superior phase response appears under the OP and EOP schemes.…”
Section: Physical Structure Of the Qd-soamentioning
confidence: 99%
“…Both theoretical and experimental studies have proven the unique capabilities of these devices. Ultrafast gain recovery [14], low noise gure of 3.5 dB [5], high saturated output power [57], pattern-eect free XGM--based wavelength conversion up to 160 Gbits/s [8], and capability of operation at Tbits/s speeds in presence of a control signal [9] are among these capabilities.…”
Section: Introductionmentioning
confidence: 99%